Application of a dedicated surface coil in dental MRI provides superior image quality in comparison with a standard coil - Gradl, Joseph; Pfefferle, Thorsten; Prager, Marcel; Hilgenfeld, Tim; Bäumer, Philipp; Heiland, Sabine; Bendszus, Martin; Hähnel, Stefan (Clinical neuroradiology, 2017)
Purpose: Purpose of our research was the evaluation of a dedicated dental surface coil in comparison with a standard head and neck coil for the improvement of dental magnetic resonance imaging (MRI).Materials and MethodsAxial T1-weighted spin echo MRI was performed by using a newly developed dental coil for MRI and a standard head and neck coil on five volunteers. In addition, MRI was implemented with dental coil on five patients. Using the Wilcoxon test, we compared the volunteers’ signal-to-noise ratio (SNR) of a variety of anatomical structures (e.g., hard tooth tissue, pulp tissue, bone, muscle tissue). Also subjective evaluation of image quality was performed on both volunteers and patients.ResultsCompared with the head and neck coil, the mean SNR was 3.5-fold higher on an average with the dental coil (range: from 2.7 [masseter muscle] to 4.6 [pulp tissue]). That difference was statistically significant for all evaluated structures. The higher SNR also resulted in a superior image quality as determined by subjective evaluation.ConclusionDental MRI benefits profoundly from using a dedicated dental coil.
Gesehen am 23.04.2018